Performance evaluation of space-frequency pre-filtering schemes for downlink TDD MC-CDMA systems - Silva, Adão
This paper deals with downlink space-frequency pre-filtering techniques for time division duplex MC-CDMA. We consider the use of antenna arrays at the base station (BS) and present different pre-filtering schemes for two different receiver configurations at the mobile terminal: a simple despreading receiver without channel equalization and an EGC conventional receiver. We show that the space-frequency pre-filtering approaches proposed allow to format the transmitted signals so that the multiple access interference at mobile terminals is reduced allowing to transfer the most computational complexity from mobile terminal (MT) to the base station. One important issue for all pre-filtering scheme is that their effectiveness relies on the accuracy of the uplink channel estimates in modeling the downlink channel. Therefore, we evaluate the performance of both schemes in scenarios where the channel changes between an uplink and downlink slot, in order to obtain the performance penalties as a function of the time separation between the uplink (UL) and downlink (DL) slots. ©2004 IEEE.